2000
DOI: 10.1016/s0370-2693(00)00927-8
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism of quark liquid

Abstract: Usually it is believed that the Hartree-Fock state of quark matter is a Fermi gas state with no polarisation of spins. We examine the possibility of the polarised quark liquid interacting with the one-gluon-exchange interaction.It is suggested that the Hartree-Fock state shows a spontaneous magnetic instability at low densities through the same mechanism as the appearance of ferromagnetism in electron gas. Metastability of the polarised quark liquid is also discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
246
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(253 citation statements)
references
References 16 publications
(17 reference statements)
7
246
0
Order By: Relevance
“…Actually Yang & Luo (1983) found that the quark-cluster phase with parallel spins is energetically favored due to the color-magnetic interaction and that the correspondent Curie temperature is ∼10 2 MeV. The ferromagnetism issue has also been noted recently by Tatsumi (2000), who suggested that the Hartree-Fock state with the inclusion of spin polarization shows a spontaneous magnetic instability at low densities through the same mechanism as in electron gas. (2) The calculation of the cooling behavior of strange stars should include the energy release as quark matter solidifies.…”
Section: Discussionmentioning
confidence: 87%
“…Actually Yang & Luo (1983) found that the quark-cluster phase with parallel spins is energetically favored due to the color-magnetic interaction and that the correspondent Curie temperature is ∼10 2 MeV. The ferromagnetism issue has also been noted recently by Tatsumi (2000), who suggested that the Hartree-Fock state with the inclusion of spin polarization shows a spontaneous magnetic instability at low densities through the same mechanism as in electron gas. (2) The calculation of the cooling behavior of strange stars should include the energy release as quark matter solidifies.…”
Section: Discussionmentioning
confidence: 87%
“…Besides, there might be some additional mechanism to sustain the magnetic field from back-reaction of charged particles [8]. Also, it is worth mentioning that the quark matter ground state could be ferromagnetic [9], which would further enhance the initially generated magnetic field.…”
Section: Yoshimasa Hidakamentioning
confidence: 99%
“…We have considered the possibility of ferromagnetism in quark matter interacting with the one-gluon-exchange (OGE) interaction [5] or with an effective interaction [6], and suggested that quark matter has a potentiality to be spontaneously polarized. To understand the magnetic properties of quark matter more realistically , especially near the critical point, some non-perturbative consideration about the instability of the Fermi surface is indispensable.…”
Section: Relativistic Ferromagnetismmentioning
confidence: 99%